A Diverse and Dynamic Region : Taking Stock of Social Assistance Performance in East Asia and the Pacific - World Bank (Washington, DC, 2014)
East Asia and the Pacific is a particularly diverse region. It includes some of the largest and most populated countries in the world such as China and Indonesia as well as small Pacific islands. Over the past decade, there has been a growing interest in undertaking reforms to strengthen social protection systems in the region, not only as crisis response tools. The primary objective of this study is to provide a comparative review of the financing, structure and performance of social protection programs in the East Asia region. The region is very diverse and this study seeks to enhance understanding of regional expenditure patterns in social protection, and to provide insights in the performance of social assistance programs in particular. Regional studies of this kind are challenging for a number of reasons, and this particular study was no exception. The performance of social assistance programs will be measured in terms of coverage, targeting accuracy, generosity of the benefit levels and impacts on poverty and inequality. The report uses data from household surveys to assess the performance of social assistance programs. There are, however, some important data related caveats to keep in mind when interpreting the results.